A Prospective Cohort Study Evaluating the Ability of Anticipated Pain, Perceived Analgesic Needs, and Psychological Traits to Predict Pain and Analgesic Usage following Cesarean Delivery - Brendan Carvalho; Ming Zheng; Scott Harter; Pervez Sultan (Anesthesiology Research and Practice)
Introduction. This study aimed to determine if preoperative psychological tests combined with simple pain prediction ratings could predict pain intensity and analgesic usage following cesarean delivery (CD). Methods. 50 healthy women undergoing scheduled CD with spinal anesthesia comprised the prospective study cohort. Preoperative predictors included 4 validated psychological questionnaires (Anxiety Sensitivity Index (ASI), Fear of Pain (FPQ), Pain Catastrophizing Scale, and Eysenck Personality Questionnaire) and 3 simple ratings: expected postoperative pain (0–10), anticipated analgesic threshold (0–10), and perceived analgesic needs (0–10). Postoperative outcome measures included post-CD pain (combined rest and movement) and opioid used for the 48-hour study period. Results. Bivariate correlations were significant with expected pain and opioid usage (r=0.349), anticipated analgesic threshold and post-CD pain (r=-0.349), and perceived analgesic needs and post-CD pain (r=0.313). Multiple linear regression analysis found that expected postoperative pain and anticipated analgesic needs contributed to post-CD pain prediction modeling (R2=0.443, p<0.0001); expected postoperative pain, ASI, and FPQ were associated with opioid usage (R2=0.421, p<0.0001). Conclusion. Preoperative psychological tests combined with simple pain prediction ratings accounted for 44% and 42% of pain and analgesic use variance, respectively. Preoperatively determined expected postoperative pain and perceived analgesic needs appear to be useful predictors for post-CD pain and analgesic requirements.